La valeur des territoires au Brésil : le cas des favelas de Rio de Janeiro - Michael Chetry (EchoGéo)
The financialization of urban space is today in at the heart of studies on the city and leads to a growing interest about the value of space. The value of space is usually considered from an economic perspective, which focuses on the monetary value of space, its exchange value. At the opposite, we prioritise in this article a social approach of the value of space, which focuses on its use value. In this context, we propose analysing the value of space by mobilising the contributions of the notion of territory and the results of several researches conducted in the favelas of Rio de Janeiro. It emerges that favelas are territories with multiple values, which differ according to their characteristics, the uses and representations of the actors who take place in these territories. Moreover, the approach based on the value of territories is particularly rich in shedding light on the dynamics of the commodification of space that are at work. The case of the favelas, perceived in the common sense as territory without value, highlights the conflicts around the appropriation of space and the obstacles at the capitalist domination of space.